Carbon dioxide insufflation is associated with increased serrated polyp detection rate when compared to room air insufflation during screening colonoscopy - Riverso, Michael; Perbtani, Yaseen B.; Shuster, Jonathan J. D.; Chakraborty, Joydeep; Brar, Tony S.; Agarwal, Mitali; Zhang, Han; Gupte, Anand; Chauhan, Shailendra S.; Forsmark, Christopher E.; Draganov, Peter V.; Yang, Dennis (Endoscopy International Open, 2017)
Background and study aims Sessile serrated adenomas (SSA) and traditional serrated adenomas (TSA) have been increasingly recognized as precursors of colorectal cancer. The aim of this study was to compare the effect of carbon dioxide insufflation (CO2I) vs. room air insufflation (AI) on serrated polyp detection rate (SPDR) and to identify factors associated with SPDR. Patients and methods Single-center retrospective cohort study of 2083 screening colonoscopies performed with AI (November 2011 through January 2013) or CO2I (February 2013 to June 2015). Data on demographics, procedure characteristics and histology results were obtained from a prospectively maintained endoscopy database and chart review. SPDR was defined as proportion of colonoscopies in which ≥ 1 SSA, TSA or hyperplastic polyp (HP) ≥ 10 mm in the right colon was detected. Multi-variate analysis (MVA) was performed to identify predictors of SPDR. Results A total of 131 histologically confirmed serrated polyps (129 SSA, 2 TSA and 0 HP ≥ 10 mm) were detected. SPDR was higher with CO2I vs. AI (4.8 % vs. 1.4 %; P < 0.0001). On MVA, CO2I was associated with higher SPDR when compared to AI (OR: 9.52; 95 % CI: 3.05 – 30.3). Both higher body mass index (OR 1.05; 95 % CI:1.02 – 1.09) and longer colonoscope withdrawal time (OR 1.11; 95 % CI: 1.07 – 1.16) were also associated with higher SPDR.Conclusion CO2I is associated with higher SPDR when compared to AI during screening colonoscopy. While the mechanism remains unknown, we speculate that the favorable gas characteristics of CO2 compared to room air results in improved polyp detection by optimizing bowel insufflation. These findings suggest an additional reason to prefer the use of CO2I over AI during colonoscopy.